Antiretroviral Therapy Adherence, Functional Independence, and Falls among People with HIV. Issue 3 (1st July 2021) - Armstead, Amber B.; Wilkerson, J. Michael; Gemeinhardt, Gretchen; Nyitray, Alan; Collins, Diane M.
Abstract: Chronic disease management coupled with education may improve outcomes for those with chronic disease. As Human Immunodeficiency Virus (HIV) is now a chronic disease, addressing the needs of as people living with HIV (PLWH) is essential as they experience an accelerated aging process due to the mechanisms of the disease and medications taken. Although studies exist on the management of chronic HIV, few discuss the implications of medication adherence and activities of daily living related to falls among PLWH. To inform occupational therapy services for PLWH, this case-control study used extracted data from the electronic medical records of PLWH who had received occupational therapy (OT) at a large academic hospital. Two-hundred-and-four subjects were included in the final dataset; sixty-eight were cases that reported a fall within the last 12 months, while 136 were controls which were PLWH who had not sustained a fall. The association between falls and antiretroviral therapy adherence indicated males who were ART non-adherent and had balance deficits were more likely to fall. The association between ADL dysfunction and falls among PLWH showed those more likely to fall had moderate ADL dysfunction and balance deficits. The findings suggest further examination of the person factors of PLWH who are categorized clinically as non-adherent with antiretroviral therapy and have ADL dysfunction may improve health outcomes and reduce falls when paired with occupation-based interventions.